Central Banking in the Digital Age: Exploring Public Perception and Regulatory Strategies for the Digital Euro - Maria-Emilia DINCULEANĂ (Finanţe: Provocările viitorului)
This study examines the emergence and implications of Central Bank Digital Currencies (CBDCs), with a specific focus on the proposed digital euro by the European Central Bank (ECB). As digital payments become increasingly integral to the global economy, central banks are exploring CBDCs to enhance payment efficiency, foster financial inclusion, and maintain monetary integrity amid growing competition from private digital currencies. The research provides an in-depth analysis of the potential benefits and challenges of implementing a digital euro, emphasizing its significance for the eurozone’s financial landscape. Through comparative case studies of various countries that have adopted CBDCs, such as China’s digital yuan, Sweden’s e-Krona, and Nigeria’s eNaira, this study highlights diverse public responses and the importance of addressing concerns related to privacy, security, and accessibility. The findings underscore that successful implementation of the digital euro hinges on its technical design, user experience, and the establishment of a robust regulatory framework. Furthermore, the ECB's strategic approach to engaging stakeholders and promoting public awareness is critical for building trust and ensuring broad adoption. Ultimately, this research concludes that while the digital euro presents a unique opportunity to modernize Europe's payment systems and enhance the euro's international standing, it necessitates careful consideration of associated risks and proactive policy measures. The study contributes to the ongoing discourse on CBDCs, offering insights into the future of digital finance and the potential for creating a resilient and inclusive financial ecosystem.